2021
DOI: 10.5194/nhess-21-1867-2021
|View full text |Cite
|
Sign up to set email alerts
|

Towards a compound-event-oriented climate model evaluation: a decomposition of the underlying biases in multivariate fire and heat stress hazards

Abstract: Abstract. Climate models' outputs are affected by biases that need to be detected and adjusted to model climate impacts. Many climate hazards and climate-related impacts are associated with the interaction between multiple drivers, i.e. by compound events. So far climate model biases are typically assessed based on the hazard of interest, and it is unclear how much a potential bias in the dependence of the hazard drivers contributes to the overall bias and how the biases in the drivers interact. Here, based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…5. Compound event occurrence probabilities and their future changes can be highly uncertain due to combined uncertainties in multiple drivers and associated interplay (Bevacqua, Vousdoukas, Zappa, et al, 2020;Santos et al, 2021;Villalobos-Herrera et al, 2021). In this context, event-based storylines, which explore consequences of high-impact plausible events either or both under present and future climates putting emphasis on plausibility rather than probability, can provide very effective information for improving emergency preparedness to compound events (Sillmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5. Compound event occurrence probabilities and their future changes can be highly uncertain due to combined uncertainties in multiple drivers and associated interplay (Bevacqua, Vousdoukas, Zappa, et al, 2020;Santos et al, 2021;Villalobos-Herrera et al, 2021). In this context, event-based storylines, which explore consequences of high-impact plausible events either or both under present and future climates putting emphasis on plausibility rather than probability, can provide very effective information for improving emergency preparedness to compound events (Sillmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The copula equality test can thus be used to evaluate whether the dependence structure between two distributions -for instance between models and observations -is significantly different. It has been applied to evaluate multivariate dependencies in a hydrological modelling context (Vezzoli et al 2017), to assess how well climate models represent the dependence structure between seasonal temperature and precipitation in Germany (Zscheischler and Fischer 2020) and to assess biases in multivariate hazard indicators (Villalobos-Herrera et al 2021).…”
Section: A Model Evaluation For Compound Eventsmentioning
confidence: 99%
“…We found that the use of univariate bias adjustment can lead to an over-or underestimation of future climate-related fire risks, despite the overall clear sign of climate-change induced risks, regardless of the bias-correction method employed. In fact, the way how climate models' biases affect the final risks is still a topic of discussion in the scientific community [59] and the way how changes in the dependence of the drivers will affect compound events in a warming world is a challenging task in assessing future climate risk of complex events.…”
Section: Discussionmentioning
confidence: 99%